2022
DOI: 10.1038/s41598-022-14713-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of statin treatment with hepatocellular carcinoma risk in end-stage kidney disease patients with chronic viral hepatitis

Abstract: Statin use in end-stage kidney disease (ESKD) patients are not encouraged due to low cardioprotective effects. Although the risk of hepatocellular carcinoma (HCC), a frequently occurring cancer in East Asia, is elevated in ESKD patients, the relationship between statins and HCC is not known despite its possible chemopreventive effect. The relationship between statin use and HCC development in ESKD patients with chronic hepatitis was evaluated. In total, 6165 dialysis patients with chronic hepatitis B or C were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Of the 17 systematic reviews listed in Table 1, 25 RSC studies were selected for subgroup meta-analysis. In addition, six RSCs not selected in the systematic reviews were secured using a similar articles option provided by PubMed [28,[31][32][33][34][35]. After excluding eight duplicated articles (Table 2), 23 RCS with 28 cohorts were finally selected for subgroup meta-analysis (Figure 1) [28,.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 systematic reviews listed in Table 1, 25 RSC studies were selected for subgroup meta-analysis. In addition, six RSCs not selected in the systematic reviews were secured using a similar articles option provided by PubMed [28,[31][32][33][34][35]. After excluding eight duplicated articles (Table 2), 23 RCS with 28 cohorts were finally selected for subgroup meta-analysis (Figure 1) [28,.…”
Section: Resultsmentioning
confidence: 99%
“…177 Similarly, patients with both HBV and diabetes or end-stage renal disease on statin therapy had a significant reduction in incident HCC by 74 and 41%, respectively, compared with non-users. 178 179 In patients with HCV, statin use also reduced the risk of incident HCC by at least 49% in a similar dose-dependent manner. 71 72 180 Consistent benefits came from statin use of at least >90 cDDDs 72 180 and were independent of reduction in FIB-4 scores (aHR = 0.6, p = 0.03) and SVR (aHR = 0.51, p < 0.001).…”
Section: Statin and Hepatocellular Carcinomamentioning
confidence: 94%
“…Regulation ofAkt pathway in HCC and statin use is not new; statin inhibits Akt and YAP signaling cascade, both of which are involved in hepatic fibrogenesis and carcinogenesis, through stabilization of Retinoid X Receptor-α, a known anti-proliferative chemotherapeutic target 115,179,204. Yokohama et al found that statin reduces expression of…”
mentioning
confidence: 99%
“…Statins are competitive inhibitors of 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CoA), and they also have potential chemopreventive and cytotoxic effects on cancer cells in different types of cancers, primarily through the inhibition of the mevalonate pathway, independent of their lipid-lowering effect [7][8][9][10]. Statin use may be associated with a lower risk of HCC development in patients with hepatitis B or C infection and diabetes mellitus (DM) [11][12][13][14][15][16]. Moreover, studies that included patients undergoing liver resection for very early and early HCC (BCLC-0 and A) have demonstrated improved recurrencefree survival for patients under statin therapy [17,18].…”
Section: Of 17mentioning
confidence: 99%